2019
DOI: 10.5897/ijbc2019.1298
|View full text |Cite
|
Sign up to set email alerts
|

Threats and their relative severity and driving forces in the African Elephant range wildlife protected areas of Ethiopia

Abstract: Anthropogenic threats to five wildlife protected areas (PAs) in Ethiopia: Omo, Mago, Chebera Churchura and Kafta Sheraro National Parks, and Babille Elephant Sanctuary were studied. The study specific objectives were to: (i) establish the relative severity of threat factors to the PAs and susceptibility of the PAs; (ii) explore underlying causes of the threats; and, (iii) identify appropriate threat mitigation measures. A semi-structured questionnaire survey was administered to 25 most experienced staffs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These findings are also in line with other studies in Bale Mountain National Park the causes of fire are anthropogenic in which farmer's set fire for various activities: honey collection, agricultural land preparation, improved forage quality, and reduce suspected livestock predators [37,40] These findings in line with the study of this illegal activity in the park was confirmed environmental degradation and loss of biodiversity [42]. Similarly, anthropogenic threats to five wildlife protected areas in Ethiopia; Omo, Mago, Chebera Churchura, KSNP, and Babile Elephant Sanctuary, was studied by Mekbeb E. Tessema, Kumara [14]; gold mining in the KSNP was ranked fourth as compare. These problems are risky for the movement wildlife population within the park and it creates disturbance against the wildlife and their habitat.…”
Section: Wildlife Conservation Challengesmentioning
confidence: 76%
See 1 more Smart Citation
“…These findings are also in line with other studies in Bale Mountain National Park the causes of fire are anthropogenic in which farmer's set fire for various activities: honey collection, agricultural land preparation, improved forage quality, and reduce suspected livestock predators [37,40] These findings in line with the study of this illegal activity in the park was confirmed environmental degradation and loss of biodiversity [42]. Similarly, anthropogenic threats to five wildlife protected areas in Ethiopia; Omo, Mago, Chebera Churchura, KSNP, and Babile Elephant Sanctuary, was studied by Mekbeb E. Tessema, Kumara [14]; gold mining in the KSNP was ranked fourth as compare. These problems are risky for the movement wildlife population within the park and it creates disturbance against the wildlife and their habitat.…”
Section: Wildlife Conservation Challengesmentioning
confidence: 76%
“…Today, there are about 73 wildlife protected areas in the country under six management categories [14]: 27 national parks, 2 wildlife sanctuaries, 6 wildlife reserves, 25 controlled hunting areas, 5 biosphere reserves, and 8 community conservation areas. However, the protected areas system of the country had not been designed with scientific concepts to ensure the role in biodiversity conservation [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the country has established 73 protected areas of different categories, including 25 National Parks (Tessema, Wakjira, & Asefa, 2019). However, like the case of many African countries, several key wildlife species have shown declining trends both in population sizes and ranges of distribution due to habitat loss and fragmentation and hunting (Abune, 2000;Yalden & Largen, 1992).…”
mentioning
confidence: 99%
“…Furthermore, Ethiopia's KBAs and protected areas Ethiopia's KBAs and protected areas are home to the greatest wealth of biodiversity, endemic and/or endangered, but also are areas where small-scale intensive crop farming, livestock grazing and logging are concentrated (Vreugdenhil et Finally, the STAR metric can also be applied for cases where the drivers of the threats are not only local or national (Irwin et al 2022), such as illegal hunting and international trade in species that can impact biodiversity in Ethiopia (Tessema et al 2019). The STAR approach can be used to quantify these embedded impacts in order to discuss international responsibility for national biodiversity pressures (see Target 5 of the KM GBF, which aims to ensure that the use, harvesting and trade of wild species is sustainable, safe and legal).…”
Section: Applications and Policy Implicationsmentioning
confidence: 99%